2021
DOI: 10.3390/cancers13194975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Quality of Life after Colorectal and Lung Cancer Surgery: A Meta-Analysis

Abstract: Surgical treatment affects health-related quality of life (HRQoL) and increases fatigue symptoms in patients with lung cancer (LC) and colorectal cancer (CRC). We aimed to systematically review the effect of exercise training on HRQoL and fatigue after LC and CRC surgery. Randomized controlled trials published before 21 March 2021, were searched in PubMed, Scopus, Web of Science, SPORTDiscus and PEDro. Eligible trials compared the effect of exercise interventions initiated preoperatively or in the first 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 86 publications
3
17
0
Order By: Relevance
“…Meanwhile, other outcomes for fatigue, depression, and anxiety scores showed no significant effects observed after exercise intervention. These findings are consistent with the results of previous meta-analysis reported that no association was observed between HRQoL and exercise intervention in their RCTs’ meta-analysis [ 24 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, other outcomes for fatigue, depression, and anxiety scores showed no significant effects observed after exercise intervention. These findings are consistent with the results of previous meta-analysis reported that no association was observed between HRQoL and exercise intervention in their RCTs’ meta-analysis [ 24 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…This possible therapeutic effect is relevant because fatigue is highly prevalent among earlystage lung cancer patients [76,77], and poor preoperative HRQOL showed an association with prolonged hospital stays and a higher incidence of cardiopulmonary complications after lobectomy for lung cancer [78,79]. Our results are aligned with the strong evidence that exercise training improves HRQOL and fatigue among cancer patients [37,80].…”
Section: Discussionsupporting
confidence: 81%
“… 2 , 4 , 8 To the best of our knowledge, this is the first multicenter RCT demonstrating that a short-term preoperative home-based exercise intervention (3–4 weeks) can improve HRQoL after lung cancer surgery. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 14 17 Despite these benefits and the recommendations for routine evaluation of HRQoL in lung cancer care, 18 the effects of preoperative exercise training on postoperative HRQoL remain unknown. 11 , 13 , 15 , 17 …”
mentioning
confidence: 99%